Anatomy of performance training - Matthews, John (London ; New York : Bloomsbury Methuen Drama, 2014)
"We train because we are human and we become human because we train. This is the surprising and original conclusion of Anatomy of Performance Training, in which John Matthews shows how training is a very human response to the problems of having a body and living in the world. Using illustrative case-studies of professional practice, each chapter addresses a specific body part, offering a self-contained discussion of its symbolic and practical significance in the artistic, and commercial, activities of training. These anatomical case-studies are cross-referenced with other disciplines (such as sport, high diving, deep diving and artisan craft) to further expand our understanding of performance. Stand-alone chapters, ideal for reference, build towards an overall conclusion that the uniquely human practice of training is emerging as a new and pervasive ideology globally.Ideal for readers seeking to understand the relationship the body has with the theatre and training, or for teachers looking for a new, innovative approach to performance, Anatomy of Peformance Training is an accessible, original contribution to the philosophy of training for performance"--
Includes bibliographical references (pages 197-201) and index.
Keywords: Acting; Performing arts; Movement (Acting); PERFORMING ARTS / Acting & Auditioning